Mandatory costs by firm size thresholds: firm location, growth and death in Sri Lanka - Babatunde O. Abidoye; Peter F. Orazem; Milan Vodopivec (IZA Journal of Labor & Development, 2014)
Sri Lanka's Termination of Employment of Workmen Act (TEWA) requires that firms with 15 or more workers justify layoffs and provide generous severance pay to displaced workers, with smaller firms being exempted. Although formally subject to TEWA, firms in Export Promotion Zones (EPZs) do not face the same constraints as nonEPZ firms due to size incentives and lax labor law enforcement in that sector. In EPZ, 77% of firms have more than 15 employees while 76% of nonEPZ firms are smaller than 15 employees. Panel data on all formal sector firms between 1995 and 2003 shows that 80% of the size gap is from sorting of large firms into the EPZ. In addition, EPZ firms grow faster and are less likely to die than comparably sized nonEPZ firms. Despite its intent, TEWA lowered employment.
Keywords: J30; 330; Firing cost; Employment protection; Firm entry; Firm growth; Threshold; Export promotion zone; Sri Lanka